Robotic Surgery for the Treatment of Achalasia with Intraoperative Manometry: Case Report - Gaytan-Fuentes, Omar Felipe; Gaytan-Fuentes, Israel Abraham; Barajas-Galicia, Edith; Barba-Mendoza, Jairo Arturo; Cerón-Castillo, Ricardo; Galicia-Gómez, Teresa De Jesús; Flores Lopez, Alejandro Alberto; Padrón-Arredondo, Guillermo (British Journal of Healthcare and Medical Research, 2025)
Introduction: Achalasia, the Greek term meaning, is a disease of unknown cause in which there is a failure to relax the lower esophageal sphincter and loss of peristalsis in the distal esophagus. Achalasia was first described by Sir Thomas Willis in 1674. Clinical case: 63-year-old female with no significant history for the case. Upon admission, the patient presented dysphagia, reflux, aspiration, substernal pain, and weight loss. Endoscopy showed Schatzki ring; Type I hiatal hernia of 5 cm, grade D esophagitis (Los Angeles classification). Manometry showed an IRP -3.06; absent esophageal clearance, without evidence of hiatal hernia, with a diagnosis of probable achalasia. The SEGD presented an area of V stenosis and a Heller myotomy with Dor-type fundoplication was performed using robotic surgery. Discussion: In clinical practice, the combined use of esophagogastroduodenoscopy (EGD) and upper gastrointestinal series (SGD) helps to evaluate patients who present with dysphagia and/or regurgitation, which are the most common clinical findings in these patients. High-resolution esophageal manometry (HREM) has become an essential tool in the last decade to categorize types of esophageal achalasia with associated lack of relaxation of the lower esophageal sphincter. Current pharmacological, endoscopic and surgical treatment options aim to reduce the hypertonicity of the lower esophageal sphincter, but unfortunately, the absence of esophageal peristalsis does not restore it to normal propulsive waves. Pharmacological treatments, including calcium channel blockers or sequential injection of botulinum toxin, are usually limited to patients who are not amenable to surgical treatment and have limited effects.